Rising from within : China's search for a multilateral world and its implications for Sino-U.S. relations - Li, Mingjiang (2012)
This paper addresses a much-debated question: what impact will the rise of China have on the existing international system? The paper attempts to provide some clues for our better understanding of this issue by examining China’s views on and policy towards international multilateralism in general and some of the newly emerging multilateral mechanisms in particular, including the G20 and the BRICs. This paper concludes that while China will become more proactive in its multilateral diplomacy, in many cases selectively, and increase its influence in global multilateral settings, various concerns and constraints will make it unlikely for China to completely overhaul or even dramatically reshape the multilateral architecture at the global level. Many factors that have hindered China’s leadership role in East Asian multilateralism are likely to restrain it at the global level in the same fashion. China is likely to repeat what it has done in the East Asian regional multilateralism in the past decade: participation, engagement, pushing for cooperation in areas that would serve Chinese interests, avoiding taking excessive responsibilities, blocking initiatives that would harm its interests, and refraining from making grand proposals. In addition, China is stuck in defining its identity, and caught up between posturing as a leader of the developing world on some issues and siding with the developed countries on other policy issues. Given all these constraints, China’s involvement in global multilateralism is likely to be guided by pragmatism rather than grand visions. The paper also argues that China will most likely strive to rise from within the existing international order. Washington should be prepared to plan its China policy on this basis and Sino-U.S. relation will largely be shaped by the dynamics of contentions for power and interest, as well as cooperation and coordination between China and the United States in various multilateral institutions.